ATPase-dependent role of the atypical kinase Rio2 on the evolving pre-40S ribosomal subunit - Ferreira-Cerca, Sébastien; Schäfer, Thorsten; Wesseling, Anne-Maria; Hurt, Ed (Nature structural & molecular biology, 2012)
Ribosome synthesis involves dynamic association of ribosome-biogenesis factors with evolving preribosomal particles. Rio2 is an atypical protein kinase required for pre-40S subunit maturation. We report the crystal structure of eukaryotic Rio2-ATP-Mg2+ complex. The active site contains ADP-Mg2+ and a phosphoaspartate intermediate typically found in Na+, K+ and Ca2+ ATPases but not protein kinases. Consistent with this finding, ctRio2 exhibits a robust ATPase activity in vitro. In vivo, Rio2 docks on the ribosome, with its active site occluded and its flexible loop positioned to interact with the pre-40S subunit. Moreover, Rio2 catalytic activity is required for its dissociation from the ribosome, a necessary step in pre-40S maturation. We propose that phosphoryl transfer from ATP to Asp257 in Rio2's active site and subsequent hydrolysis of the aspartylphosphate could be a trigger to power late cytoplasmic 40S subunit biogenesis.